Food and Reproductive Bioecology as a subsidy for the cultivation of the fish Centropomus undecimalis (Teleostei: Centropomidae) in Brazil: A Systematic Review (Research, Society and Development, 2021)
Several studies have been carried out in Brazil with different approaches for the bioecological evaluations of Centropomus undecimalis (Bloch, 1792), a fish commonly known as sea bass or chamois. These studies describe the population dynamics of the species from data such as weight, age/growth, diet and reproduction. In this context, the objective of this work was to carry out a literature review on food and reproductive bioecology as a subsidy for the cultivation of C. undecimalis in Brazil. The literature review was carried out systematically using the Scielo digital library (Scientific Electronic Library Online), Google Scholar and ResearchGate, containing the following descriptors in Portuguese: “Centropomus undecimalis”, “sea bass”, “camurim’; “sea bass” “bioecology”; “eating habits”, “diet”, “reproduction”; “reproductive biology” and “reproductive aspects”, with the help of Boolean operators “and”, “or” and “and not” and in the period between 2006 and 2021. A total of 728 articles were identified related to different aspects of the bioecology of C. undecimalis, among them, only 24 articles, identified as eligible for this systematic review, published in national and international journals, were selected. The results show that sea bass is a carnivorous fish with a piscivorous tendency, which provides a broad understanding of the nutritional requirement of the species for the preparation of balanced rations, and that, in Brazil, studies that describe and characterize reproduction, in addition to cropping systems for sea bass, they are still scarce.